Projeto Integrador Interdisciplinar na área Contábil: análise do desenvolvimento das competências pessoais, profissionais, interpessoais e sociais - Bottcher, Eliane Margarete Antonio (2022)
Technology has driven society development at a fast pace, entailing person, professional, interpersonal and social changes. In this context, the education, with its traditional methodologies, does not meet the necessities of fully preparing the individual person in every aspect of their life. The education and learning process was focused in systematic knowledge, not allowing the development of skills to keep up with the evolution and to overcome challenges imposed in face of this new scenario. Thus, this paper has the objective of evaluate the contribution in the development of personal, interpersonal, professional and social competences addressed by Zabala and Arnau (2014), in scholars of Accounting Sciences course, since the implementation of the interdisciplinary integrator project. The methodologic procedures of this paper classify themselves, due to its objectives as explanatory, with a qualitative approach and the application of a participatory action research. Data collection was done from field notes and semi-structured Interviews with focal groups (faculty and student body) and the results were evaluated by contents analysis. The action research took place during the year 2021, in the third and fourth terms, corresponding to the first and second semester respectively. The results in terms of planning and execution of interdisciplinary integrator projects are challenging due to the lack of knowledge, experience and templates in the accounting area. Nonetheless, it is evident that, with a well-structured plan and a committed staff, it is possible to evolve with the establishing of a more dynamic education and the development and growth of students. Flaws occurred during the evaluation model, deadline problems, participants availabilities to polls and interviews, faculty schedule conciliation. However, there were positive aspects such as: integration between professors and scholars, learning due to applying concepts in the solution of actual problems of professional activities and team work. The research also highlights the specific skills developed due to the four dimensions in study. Bases on the findings, it was concluded that interdisciplinary methodologies, due to integrator projects on the Accounting Sciences course which involve the student in the development of knowledge, contribute to develop skills in the professional, personal, social and interpersonal areas of the students, preparing them in whole to handle the adversities and hardships imposed to their lives at in a technological era. It was clearly perceived that the scholars, beyond grasping the concepts, observed the reality of the professional activity and how it is developed on a day-to-day basis. Furthermore, they learn to pursue new ways and solutions to obstacles encountered, develop the capacity to listen and speak, thin and question theirs and others way of thinking with respect and maturity. Start overcome fears, difficulties, get to know and control their emotions, communicate and perceive their own evolution. Become stronger knowing their limits, knowing to deal with unexpected situations and to believe in their social, technical and intellectual, emotional and sentimental capacities and skills.